2020
DOI: 10.3389/fphys.2020.01076
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Oxalate-Induced Acute Kidney Injury Associated With Glomerular and Tubulointerstitial Damage in Rats

Abstract: Acute crystalline nephropathy is closely related to tubulointerstitial injury, but few studies have investigated glomerular changes in this condition. Thus, in the current study, we investigated the factors involved in glomerular and tubulointerstitial injury in an experimental model of crystalline-induced acute kidney injury (AKI). We treated male Wistar rats with a single injection of sodium oxalate (NaOx, 7 mg•100 g −1 •day −1 , resuspended in 0.9% NaCl solution, i.p.) or vehicle (control). After 24 h of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
(84 reference statements)
2
11
0
Order By: Relevance
“…Furthermore, early diabetes amplified Acta2 gene expression. These results are consistent with other studies that reported increased profibrotic mRNA expression during AKI 56 . Here, we highlight that early diabetes aggravated the profibrotic mRNA expression induced by renal IR.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, early diabetes amplified Acta2 gene expression. These results are consistent with other studies that reported increased profibrotic mRNA expression during AKI 56 . Here, we highlight that early diabetes aggravated the profibrotic mRNA expression induced by renal IR.…”
Section: Discussionsupporting
confidence: 94%
“…The experiments were carried out following the manufacturer’s instructions, and the urine protein concentration was normalized to the urine creatinine concentration. The bands were assessed by optical densitometry using ImageJ software (National Institutes of Health (NIH), Bethesda, MD, USA) 56 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, early diabetes ampli ed the α-SMA gene expression. These results are consistent with other studies that reported increased pro brotic mRNA expression during AKI [23] and myo broblast recruitment, extracellular matrix deposition and subsequent tubulointerstitial brosis in DKD [6]. Here, we highlight that early diabetes aggravated the pro brotic mRNA expression induced by renal IR.…”
Section: Discussionsupporting
confidence: 93%
“…The experiments were carried out following the manufacturer's instructions, and the urine protein concentration was normalized to the urine creatinine concentration. The bands were assessed by optical densitometry using ImageJ software (National Institutes of Health (NIH), Bethesda, MD, USA) [23].…”
Section: Kidney Function Analysismentioning
confidence: 99%
See 1 more Smart Citation